Ответы и объяснения

  • Katyuha85
  • почетный грамотей
2013-02-09T14:40:23+00:00

√(36b)-√(16b)+2√b = 6√b -4√b +2√b = 4√b

 

√(81b)-√(25b)+3√b = 9√b -5√b + 3√b = 7√b

 

(3√8+√18)*√2 = (3√(2*4)+√(9*2))*√2 = (6√2 + 3√2)*√2 = 6*2 + 3*2 = 12+6=18

или так:

(3√8+√18)*√2 =3√(8*2)+√(18*2) = 3√16 + √36 = 3*4 + 6 =12+6=18

 

(2а-√b)(2a+√b)=4a²-b

 

(√3 + √2)² - √24 = 3+2√6+2-2√6 = 3+2 = 5

 

√3(2√12+√48)=2√36 + √144 = 2*6+12 = 12+12 = 24

 

(√a+3b)(√a-3b)=a-9b²

 

(√5-√2)² +√40=5-2√10+2+2√10 = 5+2 =7

2013-02-09T14:47:47+00:00

1. a) \sqrt{36b}-\sqrt{16b}+2\sqrt{b}=6\sqrt{b}-4\sqrt{b}+2\sqrt{b}=4\sqrt{b}

   

     b) \sqrt{81b}-\sqrt{25b}+3\sqrt{b}=9\sqrt{b}-5\sqrt{b}+3\sqrt{b}=7\sqrt{b}

 

2. a)(3\sqrt{8}+\sqrt{18})*\sqrt{2}=3\sqrt{16}+\sqrt{36}=12+6=18

 

     б)(2a-\sqrt{b})(2a+\sqrt{b})=4a^{2}-b

 

     в) (\sqrt{3}+\sqrt{2})^2-\sqrt{24}=3+2\sqrt{6}+2-2\sqrt{6}=5

 

a) \sqrt{3}*(2\sqrt{12}+\sqrt{48})=2\sqrt{36}+\sqrt{144}=12+12=24

 

б) (\sqrt{a}+3b)(\sqrt{a}-3b)=a-9b^2

 

в)(\sqrt{5}-\sqrt{2})^2+\sqrt{40}=5-2\sqrt{10}+2+2\sqrt{10}=7